Cesarean scar ectopic pregnancy: invasion of the bladder wall detected by magnetic resonance imaging - Caserta,Nelson Marcio Gomes (2017)
Abstract Although cesarean scar ectopic pregnancy continues to be the rarest form of ectopic pregnancy, its incidence is increasing because of the worldwide increase in the number of cesarean deliveries. If the diagnosis is delayed, there is a high risk of severe hemorrhage and death, whereas early diagnosis can minimize the complications associated with the condition. Here, we report a case in which invasion of the bladder wall was identified by magnetic resonance imaging.